2021
DOI: 10.1039/d1bm00970b
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polycaprolactone metallopolymer–antibiotic bioconjugates containing phenylboronic acid and cobaltocenium for antimicrobial application

Abstract: This paper reports antimicrobial metallopolymers containing biodegradable polycaprolactone as the backbone with boronic acid and cobaltocenium as the side chain. While boronic acid promotes interactions with bacterial cells via boronolectin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…As an emerging class of polyelectrolyte, metallo-polyelectrolytes , have been widely studied in recent years. The presence of metal components may endow the resulted metallo-polyelectrolyte with more functions and enable their applications in different fields, such as biomedicine, drug delivery, , energy conversion, , and so on. Furthermore, the unique chemical structure of charged metallo moieties and their affinity with counterions make metallo-polyelectrolyte different from their organic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging class of polyelectrolyte, metallo-polyelectrolytes , have been widely studied in recent years. The presence of metal components may endow the resulted metallo-polyelectrolyte with more functions and enable their applications in different fields, such as biomedicine, drug delivery, , energy conversion, , and so on. Furthermore, the unique chemical structure of charged metallo moieties and their affinity with counterions make metallo-polyelectrolyte different from their organic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that cationic cobaltocenium units incorporating β-lactam antibiotics could interact with negatively charged bacterial cell membranes through electrostatic attraction, releasing antibiotics and subsequently damaging the cell wall synthesis . It was also shown that the addition of boronic acid moieties would promote boron–polyol interactions (boronolectin) with lipopolysaccharides on the outer leaflets of cell membranes of Gram-negative bacteria, , which, therefore, could exhibit higher efficacy in combating bacteria. Both DN–PAAm and DN–PAPBA hydrogels were immersed in an aqueous solution with 10 μg of penicillin G for the antibiotic conjugation to cobaltocenium moieties.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Cobaltocenium-containing polymers have been considered potential candidates for the applications of functional polyelectrolytes. The charged nature and the counterion-dependent solubility on cobaltocenium moieties could expand the utilities of this class of cationic polymers in various fields, including healthcare applications. We reported a class of cationic cobaltocenium-containing polyelectrolytes as antimicrobial biomaterials. Different from most antimicrobial polymers based on quaternary ammonium, these novel polyelectrolytes rely on metal cations to directly interact with cell membranes. However, most metal-containing hydrogels are very soft (typically with compressive stress in the range of hundreds of kilopascal), except those using metals as chelating agents for binding ligands to construct networks. , …”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of antibiotic potentiation were investigated via enzymatic hydrolysis, outer membrane permeabilization, membrane depolarization, and efflux pumps. Although bioconjugates of metallopolymers via electrostatic interactions have been reported, [36,[43][44][45][46][47] the current work investigated, for the first time, the effective utilization of the combinations of cationic metallopolymers with the existing drugs against both planktonic and stationary phase Gram-negative bacterial cells as well as bacterial biofilms. We focused on the synthetic polymer-antibiotic combinations exhibiting the ability to inhibit the growth of bacteria, high antibiofilm efficacy, and mechanisms of potentiation while maintaining low toxicity toward mammalian cells.…”
Section: Introductionmentioning
confidence: 99%